Novel Synthetic Polyamines Have Potent Antimalarial Activities in vitro and in vivo by Decreasing Intracellular Spermidine and Spermine Concentrations - El Bissati, Kamal; Redel, Henry; Ting, Li-Min; Lykins, Joseph D.; McPhillie, Martin J.; Upadhya, Rajendra; Woster, Patrick M.; Yarlett, Nigel; Kim, Kami; Weiss, Louis M. (Frontiers in Cellular and Infection Microbiology, 2019)
Twenty-two compounds belonging to several classes of polyamine analogues have been examined for their ability to inhibit the growth of the human malaria parasite Plasmodium falciparum in vitro and in vivo. Four lead compounds from the sub-series of thiourea and one compound from urea-based analogues were found to be potent inhibitors of both chloroquine-resistant (Dd2) and chloroquine-sensitive (3D7) strains of Plasmodium with IC50 values ranging from 150-460 nM. In addition, the compound RHW, N1, N7-bis (3-(cyclohexylmethylamino) propyl) heptane-1,7-diamine tetrabromide was found to inhibit Dd2 with IC50 at 200nM. When RHW was administered to P. yoelii-infected mice at 35 mg/kg for 4 days, it significantly reduced parasitemia. RHW was also assayed in combination with the ornithine decarboxylase inhibitor difluoromethylornithine, and the two drugs were found not to have synergistic antimalarial activity. Furthermore, these inhibitors led to decreased cellular spermidine and spermine levels in P. falciparum, suggesting that they exert their antimalarial activities by inhibition of spermidine synthase.